ANALISIS DEMOGRAFIS DAN GEOGRAFIS MAHASISWA POLITEKNIK ELBAJO COMMODUS - Kristoforus Toni Harjo; I Wayan Pio Pratama; I Putu Eka Sudarsana; Ondi Asroni; Hersanius Kurnia Peong; Angling G.C. Widiyanto; Firmanus Ardiman (JURNAL AKADEMISI VOKASI, 2023)
This analysis examines the student enrollment patterns at Politeknik ELBajo Commodus, highlighting the geographic dynamics and their impact on student recruitment. Utilizing the Density-Based Spatial Clustering of Applications with Noise (DBSCAN) algorithm and calculating the physical distance between students' original schools and the Politeknik campus, the study reveals clear geographic clusters, with a high concentration of students near the Politeknik, as well as the identification of prospective students from underrepresented remote areas. The analysis results indicate that distance is a factor influencing enrollment decisions, with students living closer to the campus more likely to enroll. These findings underscore the need for tailored marketing and recruitment strategies, which not only strengthen relationships with schools in clustered areas but also create initiatives targeting remote areas. This research provides recommendations for the development of programs designed to attract students from various geographic backgrounds, as well as the importance of ongoing research to ensure the alignment of the applied strategies with the needs and preferences of prospective students. In conclusion, Politeknik ELBajo Commodus can enhance its recruitment strategies by adopting a more focused approach and a greater diversification in its student base. keywords: Geospatial Analysis, DBSCAN Clustering, Recruitment Strategies, Educational Marketing, Access to Education.